Comparative approach to the coastal edge, cartographic reconstruction, city of Arica 1876-2023 - Texidó Zlatar , Alberto (2024)
Understanding the evolution of the coastal edge in a port city in northern Chile and southern Peru and its influence on its urban form, in the absence of periodic and comparable graphic material, requires the confluence of documentary background, stories, drawings and images, which allow us to virtually reconstruct the past and with it its patterns and evolution. This text is framed within the interpretive paradigm, through a digital historical reconstruction with graphic and cartographic interpretations in order to investigate the constructive actions since the time of the Peruvian government, which today underlie the urban structure of the port city of Arica, trying to explain its procedures, forms and spaces, with project actions that supported it and can serve as a necessary background in the planning and future development of the city-port.